2002
DOI: 10.1097/00005537-200207000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Follow‐up of Fat Injection Laryngoplasty for Unilateral Vocal Cord Paralysis

Abstract: Although fat injection laryngoplasty reliably improves the voice over the short term, the long-term voice outcome is unpredictable. Additional surgeries to deal with subsequent vocal deterioration are common. The role of autologous fat injection laryngoplasty in the modern era is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
102
2
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 16 publications
2
102
2
5
Order By: Relevance
“…Fang et al 14 followed 33 patients undergoing AAI for UVFP and found that 89% of patients were satisfied with results and the satisfactory result was maintained after 12 months of follow-up, concluding that AAI improves both voice and quality of life outcomes in treated patients. Conversely, McCulloch et al 15 performed a retrospective review to analyze outcomes of 31 patients who underwent fat injection laryngoplasty and determined success rates at 1 year and 4 years to be 70% and 55%. Thirteen patients (41%) required additional procedure or injection to achieve adequate vocal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Fang et al 14 followed 33 patients undergoing AAI for UVFP and found that 89% of patients were satisfied with results and the satisfactory result was maintained after 12 months of follow-up, concluding that AAI improves both voice and quality of life outcomes in treated patients. Conversely, McCulloch et al 15 performed a retrospective review to analyze outcomes of 31 patients who underwent fat injection laryngoplasty and determined success rates at 1 year and 4 years to be 70% and 55%. Thirteen patients (41%) required additional procedure or injection to achieve adequate vocal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In cases with RLN involvement via metastatic nodes, the RLN is sometimes resected together with metastatic nodes to enable a curative operation (Tachimori et al 1995). Laryngeal reinnervation should be considered in such cases, since this procedure can prevent the progressive loss of thyroarytenoid muscle tone and stiffness, which cannot be restored reliably using other techniques (Lu et al 1996;McCulloch et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These stem cells have a high proliferative potential and the ability to differentiate down multiple lineages (Lo Cicero et al, 2008). These data suggest that a resident MSC population in vocal fold fat injections may contribute to long-term graft survival, which is suspected to occur in 55-100% of patients (McCulloch et al, 2002;Lo Cicero et al, 2008). Commercially available composite materials have also been commonly used in clinic, such as Gelfoam paste (Schramm et al, 1978), Cymetra (Milstein et al, 2005), calcium hydroxylapatite (Rosen et al, 2007), Restylane and Hylaform (Hertegard et al, 2006b).…”
Section: Scaffolds Without Cellsmentioning
confidence: 87%
“…Synthetic materials (silicone, polytetrafluoroethylene-Teflon, polyhydroxyethylmethacrylate) have largely been eschewed for clinical use because of their propensity for foreign body response, migration of material and non-biodegradability (Ejnell et al, 1984;Nakayama et al, 1993). These materials have been replaced in the clinic by more degradable biomaterials, such as collagen matrix (Kriesel et al, 2002) and fat (McCulloch et al, 2002;Lo Cicero et al, 2008). These materials have viscoelastic properties more similar to vocal mucosa than the previous injectables.…”
Section: Scaffolds Without Cellsmentioning
confidence: 99%